Voting for the Environment : the Importance of Democracy and Education in Latin America (2015)
ABSTRACT: This study found that doubling the level of democracy in Latin America reduces CO2 emissions per capita by up to 6%. This relationship is estimated by using a fixed effects panel systemof equations for 19 Latin American countries, between 1995 and 2008. Democracy acts as a conduit for increasing demands on environmental quality in Latin America, due to urban population growth and economic prosperity. Nevertheless, this study has, at least, two caveats: first it cannot unveil the long run relationship between democracy and environmental quality in the region; and, secondly, this study assumes that democracy entails positive outcomes for countries adopting this political system. RESUMEN: Este estudio encontró que duplicar el nivel de democracia en América Latina reduce las emisiones de CO2 per cápita hasta en 6%. Esta relación se calcula mediante el uso de un sistema de ecuaciones de panel con efectos fijos. La muestra incluye 19 países de América Latina, entre 1995 y 2008. Este estudio concluye que la democracia actúa como un conducto para la creciente demanda de calidad del medio ambiente en América Latina, generada por el aumento de la población urbana y prosperidad económica en la región. Sin embargo, esta investigación tiene, al menos, dos salvedades: en primer lugar, es ambigua sobre la relación de largo plazo entre democracia y calidad ambiental en la región; y, en segundo lugar, asume que la democracia trae beneficios positivos para los países que adoptan este sistema político.